Implementation of Teacher Career Development in Madrasah Aliyah Negeri - Syafaruddin Syafaruddin; Eka Susanti; Wirda Hasana (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
This study describes how to implement teacher career development at MAN Batu Bara. The objectives of this study are: (1) To determine the Career Development Planning of teachers at MAN Batu Bara, (2) To determine the implementation of the Teacher Career Development Program at MAN Batu Bara, (3) To determine the Evaluation of Teacher Career Development at MAN Batu Bara. The approach in this study was carried out with a descriptive qualitative approach. Data collection was obtained by means of observation, interviews, and documentation studies. Data analysis in this study used data reduction techniques, data presentation, and drawing conclusions/verification. Checking or checking the validity of the data used the techniques of credibility, transferability, dependability, and confirmability. The findings of this study revealed three findings, namely: (1) Planning for teacher career development at MAN Batu Bara carried out by madrasas, namely by planning for proposing the names of teachers who will be promoted to rank or class. Meanwhile, what is done by teachers is by preparing certain conditions for promotion to the rank of class, (2) The implementation of career development at MAN Batu Bara is by compiling a proposal file for promotion compiled by the teacher and recommended by the head of the Madrasa, as well as through examination of files by the head of the Madrasah. supervisor of physical documents and components of credit score assessment for teachers, (3) Evaluation of teacher career development at MAN Batu Bara conducts a self-evaluation by looking at the success of students in subjects and is also carried out by the head of the madrasa every year which is called the employee work target (SKP).